2022
DOI: 10.1002/minf.202100300
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐targeted Drug Repurposing Approach for Breast Cancer via Integrated Functional Network Analysis

Abstract: The present study focuses on the interconnected functional network of altered metabolism and EMT (epithelial to mesenchymal transition) signaling in breast cancer. We have interlinked the metabolic and EMT signaling circuits and selected Insulin receptor (IR), Integrin beta 1 (ITGB1), and CD36 as target proteins based on network analysis. Extensive computational approaches discerned the potential drug molecules from the library of 1293 FDA‐approved drugs to block all three target proteins. Using molecular dock… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…Given the oral bioavailability, inability to cross the blood brain barrier (BBB) and the safety pro le of Naldemedine, the drug presents a good choice for repositioning. Indeed, Naldemedine showed potential for drug repurposing against a number of diseases and targets, including breast cancer, COVID-19 [119,120]. Therefore, all the three drugs considered can be repurposed to target hTS.…”
Section: Discussionmentioning
confidence: 99%
“…Given the oral bioavailability, inability to cross the blood brain barrier (BBB) and the safety pro le of Naldemedine, the drug presents a good choice for repositioning. Indeed, Naldemedine showed potential for drug repurposing against a number of diseases and targets, including breast cancer, COVID-19 [119,120]. Therefore, all the three drugs considered can be repurposed to target hTS.…”
Section: Discussionmentioning
confidence: 99%
“…Structure-based screening methods have contributed equally to drug repurposing efforts starting from the start of in silico [200][201][202][203] approaches such as molecular docking. [204][205][206] Generally, structurebased VS ranks potential drug molecules against the protein target of interest which leads to reduction in experimental cost. 114,[207][208][209] Thus, normally used approaches use the structure of small molecule and protein and predict the binding affinity [210][211][212] as shown in method for observing the allowed interaction of atoms and molecules over certain period has also been used in drug repurposing for virus associated cancers Figure 6A.…”
Section: Vs-based Drug Repurposing In Viral Cancersmentioning
confidence: 99%
“…Structure‐based screening methods have contributed equally to drug repurposing efforts starting from the start of in silico 200–203 approaches such as molecular docking 204–206 . Generally, structure‐based VS ranks potential drug molecules against the protein target of interest which leads to reduction in experimental cost 114,207–209 .…”
Section: ML Dl and Other Drug Repurposing Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…Contactin-1 ( CNTN -1), a neuronal cell adhesion molecular, was not only involved in the nervous system development including axon guidance, synapse formation, and nerve impulse conduction, but also played a vital role in lymphangiogenesis, lymphatic metastasis, and proliferation of many epithelial malignancies including prostate cancer, hepatocellular cancer, breast cancer, and lung cancer ( Bamodu et al, 2020 ; Cao et al, 2021 ; Chen et al, 2021 ; Kandasamy et al, 2022 ). Additionally, in our prior studies, CNTN -1 upregulation was revealed to increase metastasis, invasion, and chemoresistance in lung adenocarcinoma cells with cisplatin resistance ( Zhang et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%